Slavoj Zizek, lector de Hegel - García Quesada, George I. (2008)
In this paper we present the general aspects of Slavoj Zizek’s interpretation about G.W.F. Hegel’s philosophy. Thus, we analyse three basic axis: the relations between Hegel’s philosophy and Lacanian psychoanalysis; dialectic thought; and its responses to the poststructuralist critiques to Hegel’s thought.